2020
DOI: 10.3390/s20154079
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Beat-to-Beat Fetal Heart Rate Measurement Using Doppler Ultrasound Signal

Abstract: The most commonly used method of fetal monitoring is based on heart activity analysis. Computer-aided fetal monitoring system enables extraction of clinically important information hidden for visual interpretation—the instantaneous fetal heart rate (FHR) variability. Today’s fetal monitors are based on monitoring of mechanical activity of the fetal heart by means of Doppler ultrasound technique. The FHR is determined using autocorrelation methods, and thus it has a form of evenly spaced—every 250 ms—instantane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…From a gravitational perspective, it is likely that the placental position is relevant after 26 weeks when the specific gravity is such that the fetus' apparent weight is 0.6-0.8 of its actual weight (Sekulić et al, 2005) and, for example, a fetus with a posterior placenta would be resting on top of its placenta when its mother is lying supine. Second, we suggest that future research pertaining to maternal postural-dependent FHR changes should include beat-to-beat fHRV, which can yield insight into fetal autonomic tone that is not otherwise possible by analyzing FHR tracing morphology alone (Shuffrey et al, 2019;Kupka et al, 2020). On a related note, we encourage other innovative approaches like that of Stone et al and their investigation of the FBS with maternal postural changes (Stone et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…From a gravitational perspective, it is likely that the placental position is relevant after 26 weeks when the specific gravity is such that the fetus' apparent weight is 0.6-0.8 of its actual weight (Sekulić et al, 2005) and, for example, a fetus with a posterior placenta would be resting on top of its placenta when its mother is lying supine. Second, we suggest that future research pertaining to maternal postural-dependent FHR changes should include beat-to-beat fHRV, which can yield insight into fetal autonomic tone that is not otherwise possible by analyzing FHR tracing morphology alone (Shuffrey et al, 2019;Kupka et al, 2020). On a related note, we encourage other innovative approaches like that of Stone et al and their investigation of the FBS with maternal postural changes (Stone et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…After testing the module, data collection and analysis of the results are carried out to determine the stability and accuracy of making the module. This study also has a goal to analyze the quality of data transmission on data transmission using IoT thinger.io [30][31] [32], in the BPM 60 measurement, there are 120 FHR graphs of data on SD -Card and IoT and then the average is taken from 120 data every 2 minutes 0.14 0.10 Several studies conclude that data monitoring through IoT media and the impact of the risk of missing data will affect the making of diagnoses by doctors [33][15] [5]. it can be concluded from this research that the researcher concludes that the loss of data in this remote monitoring will be very dangerous, because the lost data will affect the actions that will be taken by the doctor.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, because the Doppler detected by the ultrasound Doppler fetal heart rate detector often contains a large amount of messy, large variability, and uneven noise, it will cause a large degree of interference to the calculation of fetal heart rate. 8 , 9 The algorithms currently used for fetal heart rate detection by ultrasound Doppler are mainly divided into autocorrelation and short-term average amplitude difference method. 10 The autocorrelation algorithm was adopted in this study to process the ultrasound Doppler of fetal heart rate, and the results showed that it can be used for the onset of fetal growth restriction during pregnancy, which provides a reference for understanding the degree of fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%